From 'therapeutic' to political education: the centrality of affective sensibility in critical pedagogy - Amsler, Sarah S. (Critical studies in education, 2011)
While the need for humanising education is pressing in neoliberal societies, the conditions for its possibility in formal institutions have become particularly cramped. A constellation of factors - the strength of neoliberal ideologies, the corporatisation of universities, the conflation of human freedom with consumer satisfaction and a wider crisis of hope in the possibility or desirability of social change - make it difficult to apply classical theories of subject-transformation to new work in critical pedagogy. In particular, the growth of interest in pedagogies of comfort (as illustrated in certain forms of 'therapeutic' education and concerns about student 'satisfaction' in universities) and resistance to critical pedagogies suggest that subjectivty has become a primary site of political struggle in education. However, it can no longer be assumed that educators can (or should) liberate students' repressed desires for humanisation by politicising curricula, pedagogy or institutions. Rather, we must work to understand the new meanings and affective conditions of critical subjectivity itself. Bringing critical theories of subject transformation together with new work on 'pedagogies of discomfort', I suggest we can create new ways of opening up possibilities for critical education that respond to neoliberal subjectivities without corresponding to or affirming them.